Le patrimoine matériel et immatériel du tissage artisanal en France - Shantty Turck (In Situ)
In 2019, following an enquiry carried out on the last handloom weavers in France, I decided to devote my doctoral research to the question of the cultural heritage of weaving. Going to weaving workshops, frequenting various salons and exhibitions, doing training programmes, visiting museums and, above all, talking with the weavers allowed me to address the issue of how this textile heritage can be recognised and appreciated today. Handloom weavers are not numerous but they maintain skills which are rooted deeply in history and manage to survive economically and culturally in a society which is not particularly favourable to them. Thanks to their perseverance and passion, they help preserve the craft culture of weaving.